Blood Parasites in Captive Parrots: Morphological Detection and Risk Analysis in Exotic Psittaciformes from East Java - Reza Yesica; Alya Nurohmah; Nofan Rickyawan; Tiara Widyaputri; Shelly Kusumarini R (Journal of Parasite Science, 2026)
Blood parasite infections in exotic birds can lead to a decline in productivity, ultimately contributing to population reductions. This study aimed to identify the species of blood parasites, determine the infection proportion, and assess the significance of body mass and cage type as risk factors for blood parasite infection in captive exotic Psittaciformes housed in Prigen and Batu, East Java, Indonesia. A total of 330 blood smear samples were collected from 165 individual birds using a simple random sampling method. Blood parasite detection was conducted via microscopic examination of stained blood smears. The infection proportion was calculated by comparing the number of infected individuals to the total number examined. The associations between bird body mass and cage type with blood parasite infection were analyzed using the chi-square test, followed by the calculation of Odds Ratio (OR) and Relative Risk (RR) using SPSS software version 27. The identified blood parasite species included Haemoproteus spp., Leucocytozoon spp., and Plasmodium spp. The overall infection proportion among the examined Psittaciformes was 7.8%. Chi-Square analysis revealed no statistically significant associations (P > 0.05) between either body mass or cage type and infections with Plasmodium spp., Leucocytozoon spp., or mixed infections involving Plasmodium spp. and Haemoproteus spp.